2008
DOI: 10.1002/wcm.715
|View full text |Cite
|
Sign up to set email alerts
|

Towards life long learning: three models for ubiquitous applications

Abstract: SummaryIn this paper, we present three experimental proof-of-concepts: First, we demonstrate a Ubiquitous Computing Framework (UCF), which is a network of interacting technologies that support humans ubiquitously. We then present practical work based on this UCF framework: TalkingPoints, which was originally developed for use at trading fairs in order to identify each participant and company via transponder and provide specific information during and after use. Finally, we propose GARFID, a concept for using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…The notion that optimal learning depends neither on visual nor auditory modalities, but rather both, reveals the bidirectional connection between sensory integration and memory dynamics. Findings not only add insights to the existing research on ubiquitous technology, but further elucidate the sensory integration theory which predicted that sight and acoustic resonance converged to facilitate learning and guide subsequent knowledge transfer ( Holzinger, et al ., 2010 ;Koedinger & Roll, 2012 ). It was found that performance accuracy was at least partly due to the overlapping of bimodal visualizations, which reinforced the existing literature on sensory integration ( Easton, Srinivas, & Greene, 1997 ;Amedi, Malach, Hendler, Peled, & Zohary, 2001 ;Amedi, Jacobson, Hendler, Malach, & Zohary, 2002 ;Ernst & Bulthoff , 2004 ;Millar & Al-Attar, 2005 ).…”
Section: Performance Accuracysupporting
confidence: 60%
See 1 more Smart Citation
“…The notion that optimal learning depends neither on visual nor auditory modalities, but rather both, reveals the bidirectional connection between sensory integration and memory dynamics. Findings not only add insights to the existing research on ubiquitous technology, but further elucidate the sensory integration theory which predicted that sight and acoustic resonance converged to facilitate learning and guide subsequent knowledge transfer ( Holzinger, et al ., 2010 ;Koedinger & Roll, 2012 ). It was found that performance accuracy was at least partly due to the overlapping of bimodal visualizations, which reinforced the existing literature on sensory integration ( Easton, Srinivas, & Greene, 1997 ;Amedi, Malach, Hendler, Peled, & Zohary, 2001 ;Amedi, Jacobson, Hendler, Malach, & Zohary, 2002 ;Ernst & Bulthoff , 2004 ;Millar & Al-Attar, 2005 ).…”
Section: Performance Accuracysupporting
confidence: 60%
“…The historical roots of these fi ndings can be traced back to the traditional theory of observational learning ( Tomasello, 2000 ;Ashcraft & Radvansky, 2010 ). Observing interactive 3D visualizations in a multimodal environment enhanced learning acquisition and abstract concept formation (e.g., Holzinger, Kickmeier-Rust, & Albert, 2009 ;Holzinger, Kickmeier-Rust, Wassertheurer, et al ., 2009 ;Holzinger, Nischelwitzer, Friedl, & Hu, 2010 ;Mujacic, et al ., 2012 ). Findings suggested a slight advantage in learning acquisition when the students had access to both visual and audio immersion compared to either modality alone.…”
Section: Performance Accuracymentioning
confidence: 99%
“…It was also important that virtual learning had the ability to take place independent of location, especially today in our knowledge-based e-society. Students should learn from other sources besides a regular PC (Holzinger, Nischelwitzer, Friedl, & Hu, 2010; Larsen, Soerensen, & Grantcharov, 2009; Sanchez, Rodriguez, Gutierrez, Preusche, & Casado, 2012). Hence, the simulator in our research project will be integrated into relevant curriculum and used extensively by students both inside and outside of their classroom (i.e., approximately 10% of in-class activities will utilize the simulator as well as substantial usage outside of class for homework and study).…”
Section: Three-dimensional (3d) Virtual Wind Turbine Simulatormentioning
confidence: 99%
“…While a number of early efforts have been made to develop MR learning materials in various fields (Abawi, Dörner, & Haller, 2005; Behringer et al , 2007; Christian et al , 2007; Mujacic, Debevc, Kosec, Bloice, & Holzinger, 2010; Holzinger, et al , 2012), cost and technological limitations have prevented wide-spread adoption. Advances in mobile computing provide great potential to continue these early efforts and develop materials that are easily accessible and distributable on popular consumer-level mobile devices (Holzinger, et al , 2010; Mujacic, et al , 2010; Holzinger, Lehner, Fassold, & Holzinger, 2011a).…”
Section: Virtual and Augmented Reality Technologiesmentioning
confidence: 99%
“…In (Mujacic et al, 2012), Modelling, Design, Development and Evaluation of a Hypervideo Application for Digital Systems Teaching is presented and discussed. The process of life-long learning, in conjunction with three different models for mobile/ubiquitous applications is discussed in (Holzinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%